System of information interactions in enterprise controlling - A. R. Khachemizov; V. I. Zarubin (Новые технологии, 2019)
In modern conditions of high dynamics of the external environment and changes in internal processes an integral requirement for enterprise management is the presence of a controlling element in the management system that would give a clear idea of the state of the management entity, without independent control effect on it (or any element of the system). The purpose of the article is to determine the content of the requirements for the system of information interactions at an enterprise and its structure. To achieve the goal, the following tasks have been solved: highlighting the features of information interactions in the context of an information network at an enterprise within the controlling system framework, identifying the main components of the information interaction system while controlling the main business processes. A system-modular approach has been used as a methodological basis of the research. Theoretical and methodological basis of the study has been formed on the basis of fundamental works of domestic and foreign scientists in the field of the theory of management of industrial enterprises; controlling theories; scientific concepts of the formation of the structural-functional model of organizational controlling; methods, models and algorithms for accounting for the influence of various factors on achieving the goals of an enterprise, making managerial decisions based on monitoring the activities of enterprises. Formulation of the basic requirements for a system of information interactions and its main components is the result of the research.